FULANI HERDSMEN AND RURAL COMMUNITIES/FARMERS CONFLICT IN NIGERA - Goddy Uwa, Osimen,; Oyindamola O, Oyewole,; Adeboye, Akinwunmi Adeboye (IJRDO - Journal of Social Science and Humanities Research, 2017)
The tension between Fulani herdsmen and farming communities has been in existence for many years, but has seen a dramatic escalation in recent times to include attacks, armed robbery, rape, kidnappings and killings by the nomads. They brutally kill natives of invaded farming communities including women and children in various states across the country. They are armed with sophisticated weapons and usually attack their target communities at a time they are most vulnerable such as at midnight or on Sundays when they are in the church, killing people indiscriminately and burning houses and looting properties. Most worrisome is the brutality and impunity with which the assailants operate without regard for the law and the sanctity of human life. Hence, an understanding of the causes and effects of the conflict between nomads and farmers in the host communities is an important step towards realizing the goals of socio-economic development policies in the country. Therefore, it is against this backdrop that the paper assessed the conflicts between herdsmen and the farmers, using a descriptive technique. It was however observed that, Farmers-herdsmen conflict which is within the agricultural sector is a major setback to the development of the sector and the nation’s economy at large and therefore, recommends that, Unless the Federal Government urgently addresses incessant encroachment of farmlands by a group called Bororo cattle rearers, and the havoc they wreck on crops, bloody clashes between the farmers and the peripatetic herdsmen would be inevitable. Consequently that, the proposed federal government policy to create grazing reserves is long overdue as this will ensure that there is access to arable and grazing land to avert constant conflict between these two user groups.